Part 2 The environmental remains (Scottish Historical and Archaeological Internet Reports, 2010)
The environmental evidence comprised carbonised plant remains, animal and fish bone, and soils and sediments. The data were collected during the initial evaluation, various set-piece excavations and watching briefs. During the main excavation, data collected by hand were supplemented by an intensive programme of soil sieving. In particular, the extensive spreads of 'garden soil' were targeted. The reports on the carbonised plant remains and the faunal remains deal with the assemblages from the main excavation and Queensberry House separately, but each considers the results in a final discussion.